Autosomal Dominant Osteopetrosis: Clinical Severity and Natural History of 94 Subjects with a Chloride Channel 7 Gene Mutation - Waguespack, Steven G.; Hui, Siu L.; DiMeglio, Linda A.; Econs, Michael J. (The journal of clinical endocrinology and metabolism, 2007)
Context: Autosomal dominant osteopetrosis (ADO) is a sclerosing bone disorder caused by heterozygous mutations in the chloride channel 7 (ClCN7) gene. The clinical manifestations of this disease have not been well characterized since the discovery of the genetic basis of ADO. Objectives: The primary objectives were to improve our understanding of ADO clinical characteristics and to study the natural history of the disease in the largest series of patients reported to date. Design and Setting: This study was primarily a retrospective cross-sectional analysis of individuals with a ClCN7 mutation that was conducted over a 4-yr period at a tertiary referral center and through family reunions. Longitudinal data on a subset of subjects were also studied. Patients and Interventions: We studied 311 subjects from 11 ADO families, including 62 individuals with ADO (patients with the classic clinical phenotype based on radiographs and/or biochemistries), 32 unaffected gene carriers (subjects with the gene mutation but no radiographic and/or biochemical phenotype), and 217 controls who did not harbor a ClCN7 gene mutation. Clinical data were collected through patient interviews and examinations, medical records, and/or self-reported responses on a questionnaire that was completed by all subjects. Main Outcome Measures: The prevalence of fracture, osteomyelitis, visual loss, and bone marrow failure was determined. Differences in clinical manifestations were analyzed according to affected vs. carrier status, age, and underlying genotype. Results: Ninety-two percent of ADO subjects had at least one sequela of the disease. Gene carriers did not have an increased risk of disease manifestations, although they were found to have significant increases in bone mineral density (P < 0.05). Compared with controls, subjects with ADO had a significantly increased prevalence of fracture (84 vs. 36%; P < 0.0001) and osteomyelitis (16 vs. 0.9%; P < 0.0001). Severe fractures (defined as ≥10 fractures of any type and/or greater than one hip/femur fracture) were identified only in ADO subjects, and osteomyelitis typically occurred in the maxilla or mandible in older adults. Visual loss, which typically had its onset in childhood, and bone marrow failure occurred in 19 and 3% of ADO subjects, respectively. Adults were more likely to manifest an ADO clinical characteristic, but no definitive genotype-phenotype relationship could be concluded. Longitudinal data suggest that the ADO clinical phenotype worsens over time. Conclusions: ADO caused by mutations in the CLCN7 gene is a frequently symptomatic disease manifested by a high rate of fracture, osteomyelitis, visual loss, and occasional bone marrow failure. The sequelae of ADO, which can be identified as early as infancy, appear to worsen over time. Fracture is the most prevalent consequence of ADO, although other more severe manifestations of disease can occur and should not be confused with recessive forms of osteopetrosis, particularly when identified in early childhood.